HYDROSTATIC FORCE ANALYSIS ON GRAVITY WEIR USING FINITE ELEMENT METHOD - Indra Pradhana - (13113104), Harsya
Nowdays, human needs of energy are increasing exponentially. As the technology constantly improved, humans are competing each other to develop a renewable energy resources. Energy in which we commonly used are in form of electricity. Minihydro Power Plant (MHP) is one of the example of renewable energy power plant. Kambangan Minihydro Power Plant is located in Desa Kambangan, Batang Regency, Central Java. To ensure the optimum output of electricity generated, all of the Minihydro Power Plant’s component must work as proper as possible. Weir is one of Minihydro Power Plant’s component in which needs to be considered. The undergraduate thesis outcome is to design a weir for the Minihydro Power Plant. The weir itself must be able to withhold water into certain elevation for the needs of power plant system, to be declared safe as the national standard suggest, sufficient enough as the availability of land, and the topography of site. Its cross surface will be plotted using coordinate with Microsoft Excel software and its 3D form will be drawn by Autodesk Inventor. After it has been drawn, the stability of weir will be calculated using manual calculation and analytical simulation using ANSYS software. For this thesis, the weir is consist of gravity weir with a round crest type and using a MDO type for the energy dissipation. Hence, we earn the weir’s specification such as, the crest’s elevation in 670 masl, the energy dissipation’s elevation in 666 masl and 664 masl, the length of the energy dissipation in 7,5 meter, and the total length of weir in 28,7 meter. It has been declared safe based on the analysis done by manual calculation and simulation.